NEURODEVELOPMENTAL OUTCOMES AFTER ANTI-VEGF TREATMENT FOR RETINOPATHY OF PREMATURITY: A SYSTEMATIC REVIEW AND META-ANALYSIS - Permaisuari, Nizma; Barliana, Julie Dewi (Indonesian Vitreoretinal Society, 2023)
Introduction: The objective of this study was to assess the neurodevelopmental outcomes in preterm infants who have undergone intravitreal anti-vascular endothelial growth factor (anti-VEGF), either as monotherapy or in combination with laser therapy, for treatment of retinopathy of prematurity (ROP). Secondary, efficacy of anti-VEGF was also evaluated. Methods: Literature search was conducted using 7 online databases (CENTRAL, PubMed, ScienceDirect, SCOPUS, EBSCO, ProQuest, and JSTOR). Studies were selected based on the established inclusion and exclusion criteria. Primary outcomes were neurodevelopmental impairment (NDI), severe NDI (sNDI), neurodevelopmental scores, and cerebral palsy (CP) incidence. Secondary outcomes included impairment and severe impairment of each domain (motor, cognitive, and language) and retreatment of ROP. Result: Seventeen studies were included. Random-effects model meta-analysis showed no differences were observed between anti-VEGF compared to control group in NDI (unadjusted odds ratio (uOR) 1.28; 95% confidence interval (CI) 0.85 to 1.94), sNDI (uOR 1.33; 95% CI 0.92 to 1.93), and CP outcomes . Meta-analysis showed insignificant result with lower overall scores, motor, cognitive, and language domains associated with anti-VEGF treatment. Secondary outcomes showed inferior cognitive impairment (OR 1.41; 95% CI: 1.03 to 1.92) and higher retreatment rate (OR 47.55; 95% CI: 12.35 to 183.09) in anti-VEGF group. Conclusion: There were no differences in neurodevelopmental outcomes between anti-VEGF and control group. Despite not causing any adverse neurodevelopmental effect, clinicians should carefully weigh the benefits and risks of anti-VEGF injection for treating infants with ROP, since it has higher retreatment rate.